2005
DOI: 10.1128/mcb.25.13.5404-5416.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NF-κB Differentially Regulates Death Receptor 5 Expression Involving Histone Deacetylase 1

Abstract: The transcription factor nuclear factor B (NF-B) regulates the expression of both antiapoptotic and proapoptotic genes. Death receptor 5 (DR5, TRAIL-R2) is a proapoptotic protein considered to be a potential target for cancer therapy, and its expression is mediated by NF-B. The mechanism of NF-B-induced DR5 expression is, however, unknown. Herein, we determined that etoposide-induced DR5 expression requires the first intronic region of the DR5 gene. Mutation of a putative NF-B binding site in this intron elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 58 publications
7
115
2
2
Order By: Relevance
“…Thus, whereas p53 may have some impact on expression of TMS1, it may be indirect. Alternatively, the regulation of TMS1 by genotoxins may involve transcriptional crosstalk between p53 and NF-kB (Webster and Perkins, 1999) as has been described for other pro-apoptotic NF-kB target genes, such as DR5 (Shetty et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, whereas p53 may have some impact on expression of TMS1, it may be indirect. Alternatively, the regulation of TMS1 by genotoxins may involve transcriptional crosstalk between p53 and NF-kB (Webster and Perkins, 1999) as has been described for other pro-apoptotic NF-kB target genes, such as DR5 (Shetty et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…DR5 is transcriptionally regulated by the tumour suppressor p53 and by NF-kB. 19 Upon silencing DAPK2, there was no change in p53 mRNA levels and both prostate cancer PC3 cells, which are p53 null, and bladder cancer T24 cells, which have an inactivating mutation in p53, can be sensitised to TRAIL by downregulating Figure S6). These data suggested that p53 was not necessary to sensitise TRAIL-resistant cells to TRAIL-induced apoptosis and we thus focused on NF-kB.…”
Section: Resultsmentioning
confidence: 99%
“…DR expression can be induced by several chemicals, which can cause either their mRNA stabilisation 23 or transcriptional upregulation by various transcription factors. 19,24 DR induction leads to an increase in the number of receptor molecules on the cell surface, thus overcoming the threshold required to sensitise cells to TRAIL cytotoxicity. As U2OS cells do not express DR4 and silencing DAPK2 leads to the upregulation of DR5 in both U2OS and A549 cells (Figure 2), we focused on the regulation of DR5 induction/expression upon DAPK2 depletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations